2019
DOI: 10.1029/2018jd029676
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Formation of a Large Lower Positive Charge Center in a Tibetan Plateau Thunderstorm

Abstract: Numerical modeling is applied to elucidate the formation mechanism of the large lower positive charge centers (LPCCs) observed during thunderstorms over the Tibetan Plateau based on the simulation of a storm at the northeastern boundary of the plateau. Four sensitivity tests were carried out to explore the impacts of inductive charging, reversal temperature, and the choice of noninductive charging scheme. The results show that the unique environmental conditions of the Qinghai‐Tibet Plateau, which include weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…This is possible, considering some recent studies suggested that the thunderstorms with strong convection could yield high-frequency lightning flashes (they are typically associated with the upper two main charge regions), but the flash size and energy (expressed by the radiation, peak current, etc.) tend to be small because strong convection and turbulence could cause the charge regions in the cloud to be small in size (Bruning and MacGorman 2013;Bruning and Thomas 2015;Wang et al 2016;Zhang et al 2017;Zheng et al 2018Zheng et al , 2019You et al 2019). The LIS data and NTBB 2528C suggest earlier peaks than those of the WWLLN data and CGLLS data in terms of their seasonal variations, which may mean that there exists significant seasonal change in the thunderstorm property in the proportions of CG lightning and strong-discharge lightning to the total lightning and the dominant position at which the lightning occurs in the vertical direction (associated with the variation in the main positive charge region, determined by the convection intensity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possible, considering some recent studies suggested that the thunderstorms with strong convection could yield high-frequency lightning flashes (they are typically associated with the upper two main charge regions), but the flash size and energy (expressed by the radiation, peak current, etc.) tend to be small because strong convection and turbulence could cause the charge regions in the cloud to be small in size (Bruning and MacGorman 2013;Bruning and Thomas 2015;Wang et al 2016;Zhang et al 2017;Zheng et al 2018Zheng et al , 2019You et al 2019). The LIS data and NTBB 2528C suggest earlier peaks than those of the WWLLN data and CGLLS data in terms of their seasonal variations, which may mean that there exists significant seasonal change in the thunderstorm property in the proportions of CG lightning and strong-discharge lightning to the total lightning and the dominant position at which the lightning occurs in the vertical direction (associated with the variation in the main positive charge region, determined by the convection intensity).…”
Section: Discussionmentioning
confidence: 99%
“…Second, recent studies have revealed that lightning discharge intensity is affected by dynamic and microphysical processes in thunderstorms. In simple terms, small (large) charged regions tend to cause small (large) or weak-intensity (strong-intensity) lightning flashes, while the size of the charged regions is affected by the convection intensity and horizontal extent (Bruning and MacGorman 2013;Beirle et al 2014;Peterson and Liu 2013;Wang et al 2016;You et al 2019;Zheng et al 2018Zheng et al , 2019. The differences in the thunderstorm properties in different regions of the TP may lead to different intensities of the lightning discharge.…”
Section: A Spatial Distribution Of Wwlln and Lis Lightning Datamentioning
confidence: 99%
“…Therefore, the tripole charge structure in the Qinghai‐Tibet Plateau is different from that of normal thunderstorm. Wang et al () used numerical modeling to simulate the formation of a large lower positive charge center (LPCC) in a Qinghai‐Tibet Plateau thunderstorm. The results showed that the unique environmental conditions of the Qinghai‐Tibet Plateau, which include weak convection and a low freezing level, are fundamental to the formation of a large LPCC.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…With this mechanism, the more compact graupel would fall away from the ice crystals to become the lower positive charge. Graupel also plays a role in thunderstorms on the central Tibetan Plateau and the Qinghai-Tibet Plateau (Qie, Kong, et al, 2005;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%